Designing brand identity : an essential guide for the whole branding team - Wheeler, Alina (John Wiley & Sons, 2013)
From research and analysis through brand strategy, design development through application design, and identity standards through launch and governance, this text offers a proven, universal five-phase process for creating and implementing effective brand identity. Enriched by new case studies showcasing successful world-class brands, this Fourth Edition brings readers up to date with a detailed look at the latest trends in branding, including social networks, mobile devices, global markets, apps, video, and virtual brands